The Influence of Principal Academic Supervision, Lead Teacher Competence, and Work Environment on Lead Teacher Capacity - Shintawati, Shintawati; Hanafie, H. M. Syadeli; Hendrayana, Aan (Newinera Publisher, 2025)
The discourse on teacher leadership in developing contexts has long suffered from a narrow gaze, obsessed with competencies, yet blind to conditions; fixated on training, yet inattentive to power. This study disrupts that pattern. Anchored in the evolving landscape of Indonesia’s Guru Penggerak (Mobilizing Teacher) program, we offer a systems-level examination of what truly drives teacher capacity in public elementary schools. Through a robust quantitative analysis, we illuminate the triadic architecture of capacity-building: principled supervision, professionally grounded competence, and an ecologically supportive work environment. The results are not subtle; together, these factors explain 93.4% of the variance in mobilizing teacher capacity. But the implication is not merely statistical. It is structural, cultural, and political. We argue that academic supervision must be reimagined, not as a mechanism of oversight but as a dialogic practice of pedagogical stewardship. Teacher competence must be untethered from static checklists and understood as a socially constructed, morally anchored, and continuously evolving enactment of professionalism. The work environment, too often treated as backdrop, is revealed here as a core determinant of whether teacher leadership is cultivated or crushed. This is not a call for more policy, it is a demand for coherence. Without structural alignment among leadership practices, professional learning ecosystems, and institutional cultures, no reform initiative, no matter how visionary, will outlive its training modules.